Tren dan Tantangan Kebijakan Pendidikan Karakter dan Anti Korupsi di Indonesia: Kajian Literatur Sosiologi Agama: Trends and Challenges of Character Education and Anti-Corruption Policy in Indonesia: A Review of the Sociology of Religion Literature - Andi Muhammad Ikbal Salam; Budi Prayetno; Usri; Muhammad Syihabbuddin Taufiq (IAIN Parepare, 2024)
This research discusses the Indonesian government's policy of strengthening character and anti-corruption education at all levels of education. The aim is to form a generation with strong morality and a deep understanding of integrity. This research uses a systematic literature review method to analyse various literature sources related to the policy and its implementation. The approaches found include the development of formal and non-formal education programmes, as well as public campaigns. The results show an increasing attention to this issue in the national curriculum. However, challenges such as limited resources, stakeholder resistance, and lack of standardised teaching methodologies still exist. The role of teachers and educational institutions also needs to be improved through continuous coaching and training. Government policy support appears to be increasing, but implementation in schools requires a comprehensive and collaborative approach. It is recommended to develop a more contextualised curriculum and strengthen cooperation between the government, schools and communities to create an educational environment that strengthens character and anti-corruption values in a sustainable manner.